Esensi Nilai-Nilai Sosial Pada Tradisi Nganta Petuloh (Studi Living Qur’an-Hadist di Desa Koto Petai Kerinci-Indonesia) - Munawaroh; Amzaludin, Amzaludin; Panagara, Fathi Hisyam; Khumairah, Eka Silfia; Fairuzah; Al Kahfi, Sidik (LPPM IAIN Sultan Amai Gorontalo, 2025)
This research aims to explore the essence of social values contained in the Nganta Petuloh tradition in the community of Koto Petai, Kerinci Regency. This tradition, which is a form of mutual cooperation and mutual assistance in the context of celebrations or celebrations, has strong roots in local culture and serves to strengthen social relations between citizens. Through interviews with local communities, the study identified values such as empathy, solidarity, and help that are internalized in daily life. The results of the study show that Nganta Petuloh plays an important role in strengthening social ties, even though it is currently facing challenges due to social changes and declining interest of the younger generation. The influence of Qur'anic teachings is also evident in this practice, reflecting how religious values are manifested in community life. To ensure the sustainability of this tradition, this study recommends preservation efforts through education and innovation that can attract the interest of new generations. Thus, Nganta Petuloh is not only a tradition, but also a vital means in building a community that is in solidarity and supporting each other.